The resolution of the Expert Council on Interstitial Lung Diseases in Systemic Scleroderma (Moscow, October 14, 2019) - S. N. Avdeev; L. P. Ananyeva; E. V. Zhilyaev; E. V. Zonova; A. A. Klimenko; O. A. Koneva; A. M. Lila; E. S. Pershina; A. A. Stremoukhov; S. A. Terpigorev; I. E. Tyurin; N. A. Shostak (Современная ревматология)
The conclusion of the Expert Council presents the results of discussing the diagnosis and therapy of interstitial lung diseases in systemic scleroderma. The reason for this discussion was the emergence of new data on the use of nintedanib in this category of patients.